“The New Italian Design” Exhibition: A new way to bring design to people - Cortés Aliaga, Gloria (Base Diseño e Innovación, 2014)
The exhibition “the new italian design”, produced an interesting encounter between the School of Design of Universidad del Desarrollo and La Moneda Cultural Center, in order to carry out an innovative and ambitious project: to bring the Milan triennale to Santiago, Chile. This led to an interesting combination among diverse disciplines, between contemporary and modern design, between the academic field and the exhibition management. A chance of openness to discussions about the opportunities to incorporate new topics to a cultural space “inhabited” by a wide and massive audience.